2002
DOI: 10.1097/01.ico.0000263127.84015.3f
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus and Methicillin-Resistant Staphylococcus epidermidis Infections in the Cornea

Abstract: Factors associated with ocular MRS colonization were long-term use of antibiotics and/or steroids, and hospitalization. Patients who had undergone keratoplasty or who had Stevens-Johnson syndrome were at increased risk of MRS keratitis. Superficial stromal infiltrations, minimal melting, and minimal stromal scarring are characteristic of MRS keratitis. Therapy for MRS keratitis is summarized. Ofloxacin, VCM, and ABK are effective in the treatment of MRS keratitis. Vancomycin eye ointment is effective as the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 5 publications
1
83
2
Order By: Relevance
“…Vancomycin has been used frequently with success, although in rare instances in-house preparations of higher strength 5% vancomycin were required. 6 Underlying medical problems are a common finding in several studies including ours where respiratory, malignant, and cerebrovascular disease was prominent. Fukuda et al 7 reported MRSA conjunctival commensals to be three times higher in chronically bedridden patients and 1.5 times greater in patients with anaemia, malignancy, and liver dysfunction when compared with normals.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Vancomycin has been used frequently with success, although in rare instances in-house preparations of higher strength 5% vancomycin were required. 6 Underlying medical problems are a common finding in several studies including ours where respiratory, malignant, and cerebrovascular disease was prominent. Fukuda et al 7 reported MRSA conjunctival commensals to be three times higher in chronically bedridden patients and 1.5 times greater in patients with anaemia, malignancy, and liver dysfunction when compared with normals.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, two centres from Japan have published more comprehensive work in this field looking at several aspects of MRSA ocular infections. 6,7 Interesting comparisons of the cases in our study and that of previous work can be made.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Reports of MRSA ophthalmic infections are numerous in the literature. They are more commonly seen in patients in neonatal ICUs [61][62][63], in post-ocular surgical patients [64][65][66][67][68][69][70][71][72][73][74][75], among healthcare workers [76,77] after corneal refractive surgery [77][78][79][80][81][82][83][84], in hospitalized pediatric patients [85], and in patients with chronic medical disease, immuno-suppression, or immunodeficiency [70,86].…”
Section: Target Populations and Transmissionmentioning
confidence: 99%
“…In cases where the treatment induced the regression of cell infiltrations, or the corneal ulcer was localized and did not progress, instillations of 3.1% vancomycin and 2% amikacin were gradually reduced to prevent drug toxicity that may influence corneal epithelialization and vascularization. When keratitis was unresponsive to these therapies, antimicrobial therapy was changed by adding 5% vancomycin ointment 8 or 0.5% moxifloxacin eye drops 4-6 times/day or as per culture and sensitivity reports, if available.…”
Section: Treatmentmentioning
confidence: 99%